Compressive Strength of Type IV Dental Stone With ZnO Nanoparticles - Ali Salah Khaza'l; Ammar Khalid AL-Noori; Marwan Zuhair Elias (University of Mosul, College of Dentistry, 2019)
Aims: To investigate the effect of different concentrations of ZnO nanoparticles on the compressive strength of type IV dental stone. Materials and methods: Total specimens of this research was 66 specimens, it was divided into 3 groups, the first one for wet strength , second group for dry strength and third groups for SEM analysis. 0.2%, 0.5% , 1.0% ,1.5% and 2.0% weight of ZnO incorporated into type IV dental stone then evaluated both wet and dry compressive strength and compare them with the control specimen and investigate it under SEM. The results of the study were analyzed statistically by (Mean ± standard deviation, ANOVA and Duncan's multiple range test) results were be considered significant at p ≤ 0.05. Results: the compressive strength decreased in comparison to control specimens this drops in strength value is not significant in wet strength while significant in dry strength. SEM image exhibited the morphology of both stone crystals and silver NPs and exhibited the distribution of NPs inside the specimens Conclusions: The study showed that, incorporation of zinc oxide nanoparticles into dental stone reduced the compressive strength property of dental stone and evenly distributed into dental stone.